If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3y = -2(y + 3) Reorder the terms: -3y = -2(3 + y) -3y = (3 * -2 + y * -2) -3y = (-6 + -2y) Solving -3y = -6 + -2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '2y' to each side of the equation. -3y + 2y = -6 + -2y + 2y Combine like terms: -3y + 2y = -1y -1y = -6 + -2y + 2y Combine like terms: -2y + 2y = 0 -1y = -6 + 0 -1y = -6 Divide each side by '-1'. y = 6 Simplifying y = 6
| 5x^3+32x-11= | | 8*14+14= | | 5x^2+32x-11=0 | | 2x+10+2x-5+x+2x=180 | | 2y-16=5+y | | 4(5x+3)-4x=-6(7-2x)+2x-5+2x | | 10+x=-11 | | -25+x=x+27 | | 6x-6=90 | | 4y-26-3y=16-20 | | 3x-6-5x=9+7 | | 4+5q=14 | | 7c*7e= | | x^2-24x+144=49 | | 100=x+0.2x | | 8-x=x+10 | | 3x-6-5=9+7 | | 2x+8=4x-18 | | x+x+1+x+2+x+3=30 | | x-(-5)=3 | | n+n+2+n+4=66 | | (18x-8)=(6x+4) | | 8(x-3)=23-2x | | 7x-(x-3)=6 | | .5(b)(2b+8)=21 | | 2g+4(3-g)=5g+19 | | x+x+1+x+2+x+3=-15 | | 4x+25=2x+49 | | 4x+36y=-12graph | | 2x+8(x-2)=4x-3(3-2x)-7 | | 3+3x=-7+x | | 6x-3(2x-4)+1=13 |